ANALISIS PELAKSANAAN STOP BUANG AIR BESAR SEMBARANGAN DI DESA BULUH CINA WILAYAH KERJA UPT PUSKESMAS PANGKALAN BARU KABUPATEN KAMPAR PROVINSI RIAU - Haryanto Haryanto; Herniwanti Herniwanti; Reno Renaldi; Endang Purnawati Rahayu; Oktavia Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The availability of latrines were environmental health problem in the village of Buluh Cina, Kampar Regency, from 1620 peoples, 312 peoples do not have family latrine as defecation tools. The purpose of research was to analyze the implementation of the Stop Open Defecation in the village of Buluh Cina Pangkalan Baru Public Health Center Working Area Kampar Regency. The method of research was qualitative with indepth interviews, observation and document review. The sampling used purposive sampling with informants were 9 respondents. The results of research were public health center had policies stopping open defecation, human resources were not sufficient, operational costs to stop open defecation were still limited, the methods used in stopping open defecation were accordance with technical guidelines, the planning or pre-triggering stage had been running, but had not implemented all indicators, implementation or the triggering stage and monitoring has been running in accordance with the technical guidelines. It can be concluded that implementation of the Stop open defecation activity in Buluh Cina Village has been carried out, in accordance with the Triggering Technical Guidelines and the RI Minister of Health Regulation No. 3 of 2014.